ANALISIS GANGGUAN HUBUNG SINGKAT PADA PANEL UTAMA TEGANGAN RENDAH GARDU C BANDARA EL TARI KUPANG UNTUK MENENTUKAN KAPASITAS PEMUTUSAN PEMUTUS TENAGA MENGGUNAKAN ETAP 12.6 - Agusthinus S. Sampeallo; Evtaleny R. Mauboy; Muhamad Iqbal (Jurnal Media Elektro, 2022)
All operational activities at the El Tari Kupang airport in meeting their electricity needs are obtained from the electricity supply from PLN. Fulfilling the electricity needs in the airport building is expected to be able to serve lighting loads, motor loads and other loads without any disturbance. The existence of disturbances such as short circuits in the electric power system can cause problems such as damage to electrical equipment and the emergence of power outages. Therefore, problems that arise like this require an analytical study to determine the short-circuit current that will occur while reducing the consequences. The purpose of this study is to determine the magnitude of the short-circuit fault current and determine the severing capacity of a power breaker in protecting the short-circuit fault current, in the event of a short-circuit fault in the low-voltage panel. Short circuit simulation results with ETAP 12.6.0 will be compared with manual calculations based on positive, negative and zero sequence impedance values from the fault location point. The results of this study note that the smallest short-circuit fault current is a 1-phase short-circuit fault to ground, with a fault current of 4.82 kA on the Switchgear 2 bus. The largest short-circuit fault current is a 3-phase short-circuit fault, with a fault current of 9 .45 kA on Switchgear 1&2 buses. Determination of the power breaker capacity on the low-voltage panel, the results of the circuit breaker (CB) breaking capacity on Bus Switchgear 1 the breaking capacity value is 10,875 kA, on Bus Switchgear 2 the breaking capacity value is 8.67 kA and on Bus Switchgear 1 & 2 the value its breaking capacity is 14,175 kA.